Erector spinae muscle responses while standing. - Ertekin, N (1981)
In 55 normal adult subjects standing erect, stable EMG responses could be recorded from the lumbar erector spinae muscles in response to unilateral sudden are abduction produced by single electrical stimuli applied to the brachial plexus at Erb's point, or to knee and ankle movement produced by stimuli to the posterior tibial nerve in the popliteal fossa.